ВИЗНАЧЕННЯ ГЕОМЕТРИЧНИХ ХАРАКТЕРИСТИК ШПУНТУ ДЛЯ РОЗРАХУНКІВ ДЕФОРМУВАННЯ ТОНКИХ СТІНОК У 2D ПОСТАНОВЦІ (Collection of scientific works «Modern structures of metal and wood», 2020)
One of the most common structural schemes used in the construction and reconstruction of berths - is a thin wall (bolverk). This system consists of a front wall and an anchor system, which includes a string and an anchor wall (or other type of anchoring device). There are some variations of the design scheme, but each of them  includes a front wall of sheet piling. The paper presents options for determining the geometric characteristics of sheet piles for use in the calculations of flat deformation  (flat  design  model).  In  the  standard  assortments  of  sheet  piling,  only  the  general geometrical  characteristics of the section such as area,  moment of  inertia,  moment of resistance, radius of inertia are given, but this is not enough for use in finite element calculations. The complex shape  of  the  cross-section  of  the  sheet  pile  (zeta,  trough,  straight,  combined  and  other  types  of cross-section)  leads  to  differences  in  the  definition  of  geometric  characteristics  and  their interpretation  in  the  flat  and  spatial  formulation  of  the  stress-strain  state.  The  paper  presents  a method for determining the geometric characteristics of the cross section for a bending rod for a flat design model. For finite element calculations, the lost complex for geotechnical calculations Midas GTS NX is used. The use of the finite element method in determining the geometric characteristics of the cross section of the sheet pile gives a relative error of up to 5% relative to the data given in the range. What is acceptable for use in further calculations of berth structures. The paper considers two options for one meter of the running wall: 1 m includes 1 tongue completely 600 mm and the second partially 400 mm; in 1 m both sheet piles on 500 mm enter. The lowest value of the moment of  inertia was obtained  for the first variant 72511 cm4, which coincides with the value  from the range by -0.26%. And for the second option, the moment of inertia is more than 12%. Therefore, the calculations should take the most unfavorable option.